Microeconomics : - Browning, Edgar K. Browning (John Wiley & Sons, Inc, 2004)
Written by distinguished authorities in the field, this book presents a practical, real-world approach to microeconomics through a wealth of applications that demonstrate the relevance of microeconomics to everyday life